1997
DOI: 10.1074/jbc.272.28.17726
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Na,K-ATPase by Protein Kinase C at Ser18 Occurs in Intact Cells but Does Not Result in Direct Inhibition of ATP Hydrolysis

Abstract: Na,K-ATPase activity has been demonstrated to be regulated by a variety of hormones in different tissues. It is known to be directly phosphorylated on its ␣-subunit, but the functional effects of protein kinases remain controversial. We have developed a sensitive, antibodybased assay for detection of the level of phosphorylation of the ␣1-isoform of rat Na,K-ATPase at the serine residue that is most readily phosphorylated by protein kinase C (PKC) in vitro, Ser 18 . By stimulation of endogenous PKC and inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
93
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 42 publications
(60 reference statements)
3
93
1
Order By: Relevance
“…This observation is in agreement with a growing number of studies, which report stimulation of Na,K-ATPase activity in response to PKC activation (Lynch et al, 1986;Hootman et al, 1987;Gupta et al, 1991;Féraille et al, 1995;Pedemonte et al, 1997) but contrasts with findings on rat ␣1 subunits in which PKC-dependent phosphorylation inhibits (Belusa et al, 1997) or does not alter (Feschenko and Sweadner, 1997) Na,K-ATPase activity. However, our study and these former studies (Belusa et al, 1997;Feschenko and Sweadner, 1997) cannot be directly compared, because we specifically studied the role of the ubiquitous Ser-16 phosphorylation site, whereas others focused on the role of the rat-specific Ser-23 phosphorylation site. Indeed, among higher vertebrates, the rat ␣1 subunit is the only one that exhibits two PKC phosphorylation sites: the ubiquitous site on Ser-16 and an additional site on Ser-23 (Feschenko and Sweadner, 1995;Béguin et al, 1996b), accounting for 80% of in vitro PKC phosphorylation in this species (Feschenko and Sweadner, 1995).…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…This observation is in agreement with a growing number of studies, which report stimulation of Na,K-ATPase activity in response to PKC activation (Lynch et al, 1986;Hootman et al, 1987;Gupta et al, 1991;Féraille et al, 1995;Pedemonte et al, 1997) but contrasts with findings on rat ␣1 subunits in which PKC-dependent phosphorylation inhibits (Belusa et al, 1997) or does not alter (Feschenko and Sweadner, 1997) Na,K-ATPase activity. However, our study and these former studies (Belusa et al, 1997;Feschenko and Sweadner, 1997) cannot be directly compared, because we specifically studied the role of the ubiquitous Ser-16 phosphorylation site, whereas others focused on the role of the rat-specific Ser-23 phosphorylation site. Indeed, among higher vertebrates, the rat ␣1 subunit is the only one that exhibits two PKC phosphorylation sites: the ubiquitous site on Ser-16 and an additional site on Ser-23 (Feschenko and Sweadner, 1995;Béguin et al, 1996b), accounting for 80% of in vitro PKC phosphorylation in this species (Feschenko and Sweadner, 1995).…”
Section: Discussioncontrasting
confidence: 48%
“…Indeed, stimulatory, inhibitory, or no effects have been attributed to PKC phosphorylation (Bertorello et al, 1991;Middleton et al, 1993;Fisone et al, 1995;Carranza et al, 1996;Feschenko and Sweadner, 1997;Pedemonte et al, 1997). In view of the multiple mechanisms that affect Na,K pump activity and the possible interplay between different signaling pathways, these conflicting results suggest that tissue-specific factors and uncontrolled experimental conditions may mask the basic function of PKC phosphorylation.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…No significant difference was noticed in the levels of the ␣1 subunit in the purified preparations. Further, we did not observe any significant difference in the phosphorylation level of ␣1 at the protein kinase C site (Ser-18) (34,35). Staining with McK1 antibody, which recognizes only non-phosphorylated ␣1, was practically identical in preparations from control and hypertonicity-treated cultures (500 mosM, NaCl) (Fig.…”
Section: Fig 1 Expression Of ␥ Splice Variants Is Selectively Contrmentioning
confidence: 82%
“…However, previous studies have shown that PKC phosphorylation of the Na + ,K + -ATPase α1-subunit is associated with either inhibition or stimulation of Na + ,K + -ATPase activity [18,39,40,41,42]. These differential effects rely on metabolic factors [43], intracellular calcium concentrations [44], PKC isoforms [38], as well as cell specific factors [45,46]. Taken together, all these results suggest that PKC phosphorylation of the α1-subunit does not directly alter Na + ,K + -ATPase intrinsic properties but rather could recruit cell-specific regulatory factors that determine the functional effect of Na + ,K + -ATPase phosphorylation.…”
Section: Discussionmentioning
confidence: 99%